Depiction of Chamunda on the exterior wall of the Antarala - Temples of India Project Team (Jio Institute, 2024)
Chamunda is depicted on the exterior wall of the antarala vestibule or antechamber) of the Undeshwar Temple, serving as the first figure encountered by devotees during the parikrama (circumambulation). Standing atop a human body, she is accompanied by two attendants and an animal. Although she possesses multiple arms, many of them are damaged. In her upper hands, she holds a sarpa (serpant), partially obscured by her jatamukuta (crown of mattered hair). Her intact right arms hold a damaru (double-headed drum) and a trishula (trident), while her left intact hands grasp a khatvanga (staff with a skull) and a bowl. She touches her lips with the finger of her left hand. At the bottom left, a seated figure is depicted holding a bowl, suggesting he is drinking from it. It is conceivable that one of the broken left hands of the goddess was carrying a munda (severed human head). The presence of the seated figure with a bowl implies he is drinking blood dripping from the severed head. Chamunda is portrayed with a skeletal body, and her belly cavity contains a scorpion. Her lower body is covered with a loin cloth.